FAKTOR PENYEBAB MENGENDAPNYA BARANG BERBAHAYA DAN PROSEDUR PEMUSNAHANNYA DI TERMINAL KARGO BANDARA SOEKARNO-HATTA - Rizaldy, Wynd; Hidayat, Didiet Rachmat; Chairuddin, Irwan (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2017)
The objective of the research is to analyze and determine the factors that cause unclaimed dangerous goods and find the right procedure of disposing them at Import warehouse line 1 area Soekarrno Hatta Airport. The research was conducted due to a lot unclaimed hazardous cargo laying at import storage terminal cargo recently. The research was using 5 (five) dimensions (Environment, Method, Equipment, Procedures, and Man Power). The method used qualitatif descriptive approach with Fishbone as a tool, then continue with five why keys to find out the solution for the main problem. Based on the result, the warehouse operators still need to improve the way of handling and storaging as well as disposing the cargo by coordinating more with other institution concerned to ensure safety compliance based on national and international regulation.